Myth, Religion, and National Identity: Mythologization in Serbia in the Period of National Crisis - Saša Nedeljković (University of Belgrade, 2016)
An attempt has been made in this paper to study the cognitive component of theisation and mythologisation in Serbia within the period of national crisis, both on institutional and individual level. The paper is based on a research initiated in 1998 and completed in 2000, thus it encompasses periods prior to, during, and after the NATO aggression. Institutional level was surveyed through texts from war editions of "The Military" magazine, while the individual one was surveyed through opinions and thoughts of the Belgrade student’s population. Research results indicate the existence of correlation between the two levels regarding ways and degrees of myth usage, as well as certain differences.